Ius Constituendum Regulation of Gambling in Indonesia: A Perspective of the Philosophy of Law Volkgeist Friedrich Carl von Savigny - Faisol; Rizky Akbar; Souad Ahmed Ezzerouali (NOVUM : JURNAL HUKUM, 2024)
This article discusses the phenomenon of gambling in Indonesia from the perspective of the Volkgeist legal philosophy of Friedrich Carl von Savigny, which asserts that law is not merely a product of formal legislation, but rather an expression of the collective spirit of a society living within local traditions and culture. Although gambling is prohibited in positive law, traditional gambling practices that are ingrained in the cultural identity of various ethnic groups indicate a tension between formal law and customary law rooted in the Volkgeist. Therefore, law enforcement against gambling needs to accommodate cultural values and local wisdom so that legal policies can be accepted and effective, as well as and maintain social harmonysocial harmony can be maintained. Future gambling regulations should be based on the understanding that the law reflects the collective spirit of society, with an approach that integrates formal legal aspects and respect for tradition, supported by cross-institutional collaboration and public education to effectively combat online gamblingto combat online gambling effectively. This holistic approach is expected to create a balance betweenbalance the supremacy of law and the preservation oflaw supremacy and preserve local values for sustainable justice and social order in Indonesia.